SALAM DAN UNGKAPAN PERPISAHAN DALAM BAHASA INGGRIS DAN BAHASA PASAN: SUATU ANALISIS KONTRASTIF - SENEWE, RINNIE; JANSEN, FRIEDA TH.; PAMANTUNG, RINA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT             The title of this research is “Salam dan Ungkapan perpisahan dalam Bahasa Inggris dan Bahasa Pasan: Suatu Analisis Kontrastif“. The study is an attempt to analyze, and describe, the contrast English and Pasan Language which focuses on Greetings and leave taking in relation to theirs forms and pattern in both languages.    Greetings and leave takings are part of talk and action while  very important in conversation, greetings is used for opening a conversation and also for establishing social relationship with the other people,  whereas leave takings is used to closing a conversation.  This research uses descriptive method and contrastive analysis. The data were taken from Library research and field research, in this case choosing informants and giving the interview.  The data were collected, analyzed ,and described, to find out the forms and patterns of Greetings and leave taking the writer used theory of  Wardhaugh (1986), Tilit  and  Bruder  (1985) , Brown and Ford (1961). After that, the data were contrasted by using Lado’s theory (1971). The results of this study is Greetings and leave taking in English and Pasan language has two forms, they are formal ad informal. The result is there are three patterns in English and four patterns in Pasan language on Greetings. The patterns of English and Pasan Leave Taking are the same as their Greetings.  Keywords: Greetings and Leave-Takings, English and Pasan Language,        Contrastive Analysis